The Influence of Gongronema latifolium and Ocimum basilicum Extracts on the Antioxidant and Physicochemical Properties of Smoked Beef Stored at Room Temperature - Anthony Pius Bassey; Olubunmi Olufemi Olusola; Ayobami Adeshola; Jumoke Folasade Ajibade (Current Research in Agricultural and Food Science Vol. 5, 2021)
Introduction: Incessant health risks associated with chemical preservatives have resorted to the need of exploring natural alternatives with antioxidant potentials in meat processing. In this study, the effect of Ocimum basilicum (OBE) and Gongronema latifolium (GLE) extracts were evaluated in smoked beef during 9 days of room storage (25±1°C). In the food industry, antioxidants which are essential properties in food preservation, are categorized into two groups: one is synthetic antioxidants such as nitrite and the second includes natural antioxidants such as plant extracts possessing antioxidant characteristics. Methodology: Beef samples were prepared from freshly cut rounds (2 kg each) allotted to four groups containing Nitrite, OBE, GLE, and OBE+GLE respectively. Prepared beef samples were subjected to physicochemical (cooking loss, yield, and colour), sensory characteristics, pH, and lipid oxidation (TBARS) analyses. Data were analyzed using descriptive statistics and ANOVA at ?0.05. Results: No significant change was observed in cooking yield and colour although higher values occurred in control samples. OBE and GLE inclusions exhibited a marked potential in sensory characteristics such as flavour, texture, tenderness, juiciness with the panelists rating the latter as the samples with higher overall acceptability. Results in the storage period showed a significant progression in TBARS and pH values in all treatments with the highest and lowest values observed in control and OBE treatments. Conclusion: GLE treated beef showed a marked efficacy throughout the storage period than the other extract-treated samples. With the need to provide natural alternatives against chemical preservatives, exploring its synergistic effects with other cheap, accessible and rich bioactive sources will be imperative in the shelf life extension of meat.